2021
DOI: 10.1038/s41598-021-92152-9
|View full text |Cite
|
Sign up to set email alerts
|

Russian forest sequesters substantially more carbon than previously reported

Abstract: Since the collapse of the Soviet Union and transition to a new forest inventory system, Russia has reported almost no change in growing stock (+ 1.8%) and biomass (+ 0.6%). Yet remote sensing products indicate increased vegetation productivity, tree cover and above-ground biomass. Here, we challenge these statistics with a combination of recent National Forest Inventory and remote sensing data to provide an alternative estimate of the growing stock of Russian forests and to assess the relative changes in post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 19 publications
6
23
0
Order By: Relevance
“…CC BY 4.0 License.In the two largest boreal and arctic countries Canada (CAN) and Russian (RUS), inversions produce a CO2 sink (average 219 and 326 TgC yr -1 ) which is systematically larger than the NIs (2 and 173 TgC yr -1 , respectively) during 2001-2019. The larger Russian sink of inversions is similar with the results of a recent analysis(Schepaschenko et al, 2021)of forest inventory data estimating a carbon accumulation of 343 TgC yr -1 from 1988 to 2014. The Russian carbon stock increase is 6.0 TgC yr -1 annually in the NI during the 2000s, smaller than the increasing CO2 sink rate of 16.4 TgC yr -1 across inversions.…”
supporting
confidence: 86%
“…CC BY 4.0 License.In the two largest boreal and arctic countries Canada (CAN) and Russian (RUS), inversions produce a CO2 sink (average 219 and 326 TgC yr -1 ) which is systematically larger than the NIs (2 and 173 TgC yr -1 , respectively) during 2001-2019. The larger Russian sink of inversions is similar with the results of a recent analysis(Schepaschenko et al, 2021)of forest inventory data estimating a carbon accumulation of 343 TgC yr -1 from 1988 to 2014. The Russian carbon stock increase is 6.0 TgC yr -1 annually in the NI during the 2000s, smaller than the increasing CO2 sink rate of 16.4 TgC yr -1 across inversions.…”
supporting
confidence: 86%
“…The work presented in this paper is focused specifically on estimation of GSV in the Russian boreal forest. The Boreal forest generally, and the Russian part in particular, is poorly inventoried [1,61] and yet its importance in our understanding of the global climate system is high [62]. Globally, the boreal forest accounts for 31% of the area, 20% of the GSV, and 13% of the above-ground biomass of all forest whereas Russia, which is dominated by boreal forest, accounts for 20% of the global forest area [63].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the boreal forest accounts for 31% of the area, 20% of the GSV, and 13% of the above-ground biomass of all forest whereas Russia, which is dominated by boreal forest, accounts for 20% of the global forest area [63]. However, a recent study based on remote sensing data has shown that the growing stock of Russian forests is 39% higher than the value of official statistics in the State Forest Register [61]. Multispectral VNIR remote sensing-based GSV estimation for boreal forest is particularly challenging because of the low canopy coverage, combined with the fact the field layer is often composed of dwarf shrubs that are spectrally not very different from the forest canopy [64].…”
Section: Introductionmentioning
confidence: 99%
“…The Russian forest sector is of great importance for the global economy in several dimensions, including climate change and carbon storage, biodiversity preservation, water regulation and soil protection, and global ecosystem services, and plays a significant role in timber supply [1,2].…”
Section: Introductionmentioning
confidence: 99%